Knowledge and Attitudes of Healthcare Workers towards Antibiotic Use and Antimicrobial Resistance in Two Major Tertiary Hospitals in Western Greece - Maria Lagadinou; Elpida Tsami; Apostolos Deligakis; Themistoklis Paraskevas; Christos Michailides; Dimitrios Velissaris; Despoina Gkentzi; Markos Marangos (MDPI AG, 2023)
Antibiotic resistance (ABR) and antimicrobial stewardship arethe two sides of the same coin that constitute a public health hydra. This study aimed to assessthe knowledge and attitude of healthcare workers (HCWs), on antibiotic use and antimicrobial resistance in Western Greece. A total of 200 healthcare workers (doctors, nurses, and others) from the two largest tertiary hospitals in Western Greece were included in our survey. HCWs seem not to decide based on patient opinion in order to prescribe antibiotics. Approximately 97% of them are aware of their main adverse effects. Remarkably, 25% of respondents prescribe antibiotics due to diagnostic uncertainty, and 32.5% of them prescribe antibiotics based on their experience. HCWs statedthat they do not report adverse effects often. Inappropriate antibiotic prescriptions were mentioned as the main reason for bacterial resistance to antimicrobials. Monitoring the patient's treatment progress, using electronic prescriptions, and adhering to international guidelines were suggested as solutions to the problem. Post Hoc analysis showed that nursing staff apply to the national guidelines (p: 0.011) and use electronic prescriptions (p: 0.003) less often compared to consultants, doctor directors, and trainees. The findings of our survey may be useful for the development of future national education programs and interventions thatmay improve healthcare workers' knowledge and ability to manage antibiotics.